COMMITMENT AS A GUARANTEE OF SUCCESS IN THE STUDENTS INDIVIDUAL WORK AT THE DEPARTMENT OF THERAPEUTIC STOMATOLOGY - Бублій, Т.Д.; Sidash, V. (World of Medicine and Biology, 2014)
The article analyzes the independent work of students of the learning process of the terms of credit-modular system. The independent work of students creates the conditions for the formation of a conscientious attitude to the educational process, education, sense of duty and responsibility, efficiency, persistence, as well as creativity and other ethical standards for decent work of the professions.